Effectiveness of Local Potential-Based Biodiversity E-booklets on Students' Critical Thinking Skills - Na'imah, Nuning Nadrotun; Widiyaningrum, Priyantini; Martuti, Nana Kariada Tri (Journal of Innovative Science Education, 2022)
Cirebon Regency is one of the areas in West Java which is located on the coast of the Java Sea and has good natural resource potential, causing the biodiversity in the Cirebon area to be relatively high and attractive, thus having potential that can be used as a learning resource. This study aims to analyze the effectiveness of implementing the local potential-based biodiversity e-booklet on critical thinking skills according to Ennis, which consists of aspects of providing simple explanations, building basic skills, concluding, further clarification, setting strategies and tactics. This research is a development research or Research and Development (R&D) that adopts the Sugiyono model (2017) with the research subject of 101 students of class X SMA Negeri 1 Losari, MAN 5 Cirebon and SMA NU Ciledug. The sampling technique was purposive sampling with a one group pre-test post-test design. The pretest and posttest questions consist of 20 multiple choice questions according to the critical thinking aspect according to Ennis. The results showed that the local potential-based biodiversity e-booklet was effective for improving critical thinking skills with the results of the N-gain test in the high category (35.67%), medium (58.53%), low (5.80%) with the average N-gain is 0.63 which is included in the medium category and classical completeness reaches 86.14%. Biodiversity e-booklets based on local potential are effectively used to improve students' critical thinking skills.